-2(3x-5)+5x=8+3(3x-2)

Simple and best practice solution for -2(3x-5)+5x=8+3(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-5)+5x=8+3(3x-2) equation:


Simplifying
-2(3x + -5) + 5x = 8 + 3(3x + -2)

Reorder the terms:
-2(-5 + 3x) + 5x = 8 + 3(3x + -2)
(-5 * -2 + 3x * -2) + 5x = 8 + 3(3x + -2)
(10 + -6x) + 5x = 8 + 3(3x + -2)

Combine like terms: -6x + 5x = -1x
10 + -1x = 8 + 3(3x + -2)

Reorder the terms:
10 + -1x = 8 + 3(-2 + 3x)
10 + -1x = 8 + (-2 * 3 + 3x * 3)
10 + -1x = 8 + (-6 + 9x)

Combine like terms: 8 + -6 = 2
10 + -1x = 2 + 9x

Solving
10 + -1x = 2 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
10 + -1x + -9x = 2 + 9x + -9x

Combine like terms: -1x + -9x = -10x
10 + -10x = 2 + 9x + -9x

Combine like terms: 9x + -9x = 0
10 + -10x = 2 + 0
10 + -10x = 2

Add '-10' to each side of the equation.
10 + -10 + -10x = 2 + -10

Combine like terms: 10 + -10 = 0
0 + -10x = 2 + -10
-10x = 2 + -10

Combine like terms: 2 + -10 = -8
-10x = -8

Divide each side by '-10'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| 6+3(5x-5)=6-4(2x+1) | | 10*n=1 | | 4x-2+6(x-4)=3+2x | | 9(7x-2)= | | 3x(x+10)+4(x+20)+5x=185-3x | | 5n-14=41 | | 4*n=1 | | 2(2y-1)+y=3 | | 2(x+4)=2(-8-x)-2x | | (2x+3)x=50 | | 13-6d/7=7 | | 2+3q=4q | | B+1=-5b+5 | | -8(32x+13)=26(16-6x) | | 2+2x-5=5(x+3) | | 6(18+5x)= | | 10=3.1 | | 5(c+12)=2c+18 | | -18x+4-12x-10=9-6x-3 | | 3w-9+2(3w+5)=-5(w+1) | | -7(1+8v)=-399 | | (10x-8)+(2x+9)= | | 4(x+3)=3x+2+x | | -2-(5-6p)= | | 9x+(y)i-5=12i+4 | | -3(-8+4n)=2(2-8n) | | -5x=-50+5(4x-10) | | 3n-144=2n-32 | | 2/3x-1=4 | | .375x-.75=.125x | | 3z-(z-4)=10 | | 100[0.05(m+5)]= |

Equations solver categories